Southern Ocean warming and Wilkes Land ice sheet retreat during the mid-Miocene - Sangiorgi, Francesca; Pross, Jörg; Brinkhuis, Henk (Nature Communications, 2018)
Ocean heat is important in forcing ice sheet retreat, yet past ocean temperature data from proximal ice sheet locations are sparse. Here, the authors present temperature reconstructions from the Wilkes Land subglacial basin during the mid-Miocene, and show that warm waters sustained ice sheet retreat 17-14.8 Ma.